2014
DOI: 10.1007/s00438-014-0898-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of WRKY family genes under biotic and abiotic stresses in Brassica rapa

Abstract: WRKY proteins constitute one of the largest transcription factor families in higher plants, and they are involved in multiple biological processes such as plant development, metabolism, and responses to biotic and abiotic stresses. Genes of this family have been well documented in response to many abiotic and biotic stresses in many plant species, but not yet against Pectobacterium carotovorum subsp. carotovorum and Fusarium oxysporum f.sp. conglutinans in any of the plants. Moreover, potentiality of a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…Although 145 WRKY TFs are found in Brassica rapa plants such as Chinese cabbage [34,35], and a senescence-related Group IIc WRKY TF BrWRKY75 is preliminarily characterized in our previous study [36], the mechanism(s) of senescence-associated WRKY TFs involved in regulating leaf senescence in Chinese flowering cabbage remains unclear. However, in the present work, searching our RNA-seq transcriptome database, a full-length WRKY gene (NP_001306245.1) showed increased expression during postharvest cabbage leaf senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Although 145 WRKY TFs are found in Brassica rapa plants such as Chinese cabbage [34,35], and a senescence-related Group IIc WRKY TF BrWRKY75 is preliminarily characterized in our previous study [36], the mechanism(s) of senescence-associated WRKY TFs involved in regulating leaf senescence in Chinese flowering cabbage remains unclear. However, in the present work, searching our RNA-seq transcriptome database, a full-length WRKY gene (NP_001306245.1) showed increased expression during postharvest cabbage leaf senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has demonstrated that WRKY genes are involved in responses to various stresses and there is now compelling evidence that WRKYs are plant transcription factors that regulate tolerance to abiotic stresses [48]. Gene expression studies have shown that 20 AtWRKY genes in Arabidopsis, 41 OsWRKY genes in rice, 66 GmWRKY genes in soybean, 41 BrWRKY genes in Brassica rapa, and 74 BnWRKY genes in rapeseed are involved in responses to abiotic stresses [14,18,34,[49][50][51]. In this study, 44 SiWRKY genes were expressed differentially in response to waterlogging and drought stresses, indicating that these genes may also be involved in responses to abiotic stresses.…”
Section: Identification Of Siwrky Genes Involved In Responses To Abiomentioning
confidence: 99%
“…In our previous study, we identified 85 MeWRKYs and analyzed their expression profiles in response to various abiotic stresses (Wei et al, 2016b). Current studies have indicated that WRKY TFs are widely involved in regulating plant abiotic stress responses, such as drought, salt stress, and ABA signaling (Rushton et al, 2012;Liu et al, 2014;Gong et al, 2015;Kayum et al, 2015;Singh & Laxmi, 2015;He et al, 2016). As a WRKY TF, abscisic acid (ABA) overly sensitive 3 (ABO3) modulates ABA-mediated stomatal closure and drought stress resistance in Arabidopsis (Ren et al, 2010).…”
Section: Introductionmentioning
confidence: 99%